The four pillars of HFrEF therapy: is it time to treat heart failure regardless of ejection fraction?. (19th December 2022) - Docherty, Kieran F; Bayes-Genis, Antoni; Butler, Javed; Coats, Andrew J S; Drazner, Mark H; Joyce, Emer; Lam, Carolyn S P
Abstract: The syndrome of heart failure (HF) has historically been dichotomized based on clinical trial inclusion criteria into patients with a reduced or preserved left ventricular ejection fraction (LVEF) using a cut-off of above or below 40%. The majority of trial evidence for the benefits of disease-modifying pharmacological therapy has been in patients with HF with reduced ejection fraction (HFrEF), i.e. those with an LVEF ≤40%. Recently, the sodium-glucose co-transporter 2 inhibitors empagliflozin and dapagliflozin have been shown to be the first drugs to improve outcomes in HF across the full spectrum of LVEF. There is, however, growing evidence that the benefits of many of the neurohumoral modulators shown to be beneficial in patients with HFrEF may extend to those with a higher LVEF above 40% but still below the normal range, i.e. HF with mildly reduced ejection fraction (HFmrEF). Whether the benefits of some of these medications also extend to patients with HF and preserved ejection fraction (HFpEF) is an area of ongoing debate. This article will review the evidence for HF treatments across the full spectrum of LVEF, provide an overview of recently updated clinical practice guidelines, and address the question whether it may now be time to treat HF with some therapies regardless of ejection fraction.